The Nature and Process of Meaning-Making in Text-Based Classroom Discussion of an American Islamic School - Parlindungan, Firman; Rodgers, Adrian (UIII Press, 2023)
This study aimed to uncover how elementary school students and their teacher make meaning as they participate in text-based classroom discussion at an American Islamic school. One English language art teacher and 20sixth grade students participated in this study. We employed a case study design with classroom observation, field notes and documentation as tools for data collection. The gathered data were analyzed qualitatively. We found that the classroom talks in discussing textual information followed the traditional I-R-E (Initiate-Respond-Evaluate) pattern in which the teacher held control over turn-taking opportunities and interpretive authority. The students’ participations in this discourse were restricted to remembering facts, rules and procedures found in the text in which their responses were limited and brief. In contrast, the classroom talks about extratextual information as well as about Islamic knowledge and values were more dialogic in which the conversational flow was not directed by the teacher. The students’ responses were longer with elaborated explanation or reasoning to support their position. Their Islamic cultural backgrounds and practices also enabled them to extend the discussion and make better sense of the text. These findings indicate that teachers’ didactic strategy in conducting text-based classroom discussion shapes whether students would have meaningful interaction or not. We subscribe to the view that meaning of text and knowledge construction are not solely derived from the text or defined by one person. Instead, they can be co-constructed in dialogic discussion that challenges various voices, tensions and conflicts between members of the class.